2014
DOI: 10.5455/2319-2003.ijbcp20141004
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin pre-treatment for pressor response to direct laryngoscopy and tracheal intubation: a randomized, double-blind, placebo controlled study

Abstract: Background: Laryngoscopy and endotracheal intubation are associated with an increase in blood pressure (BP) and heart rate (HR). The present study was conducted to evaluate the role of gabapentin in attenuation of these hemodynamic changes. Methods: Forty patients undergoing elective laparoscopic cholecystectomy under general anesthesia with standardized premedication and anesthetics were randomized to receive gabapentin or a matching placebo. The patients of Group I received gabapentin 600 mg orally 2 hrs bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…[1-,3] Various agents, including anaesthetics, analgesics, adrenergic blocking agents and vasodilators effectively attenuate this response. [6][7][8][9][10][11][12] This has been a fertile area for clinical investigation, spawning numerous studies of the various techniques which might be expected to modify the haemodynamic response to intubation. Even a transient hyper-dynamic response may cause serious complication in patients with symptomatic aortic aneurysm, recent myocardial infarction, cerebral aneurysm, or intracranial hypertension, known or suspected ischaemic heart disease is by far the most common indication for modifying the haemodynamic response to intubation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1-,3] Various agents, including anaesthetics, analgesics, adrenergic blocking agents and vasodilators effectively attenuate this response. [6][7][8][9][10][11][12] This has been a fertile area for clinical investigation, spawning numerous studies of the various techniques which might be expected to modify the haemodynamic response to intubation. Even a transient hyper-dynamic response may cause serious complication in patients with symptomatic aortic aneurysm, recent myocardial infarction, cerebral aneurysm, or intracranial hypertension, known or suspected ischaemic heart disease is by far the most common indication for modifying the haemodynamic response to intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative myocardial ischaemia has been associated with postoperative myocardial infarction, and a causal relationship has been postulated. [8,10] Therefore, elimination of ischaemia at the time of intubation might prevent infarction. Modification of the haemodynamic response to intubaton is a laudable objective and is clearly indicated in a small subgroup of patients in whom a single hyper-dynamic episode may cause a catastrophe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geeta Bhandari et al 15 conducted a study on effect of gabapentin at a dose of 900 mg on pressor response to laryngoscopy and tracheal intubation when compared to placebo. They found that 0 min after intubation the mean diastolic blood pressure and heart rate were significantly less in the gabapentin group than the placebo group whereas there was no statistically significant difference in systolic blood pressure of both the group at o min after intubation was present.…”
Section: Dose Selectionmentioning
confidence: 99%
“…3). At five minutes, the analysis included 21 studies [21][22][23][24]26,[28][29][30][32][33][34][35][36][37][38][39]41,[43][44][45]47 with 1,350 participants where the aggregated effect estimate showed an attenuated rise with gabapentin (MD -9 mmHg; 95% CI, -13 to -5; low quality). At ten minutes, the analysis included 18 studies [21][22][23]26,28,30,[32][33][34][35][36][37][38][39]41,43,44,47 with 1,244 participants where the aggregated effect estimate showed an attenuated rise with gabapentin (MD, -8 mmHg; 95% CI, -11 to -5; low quality).…”
Section: Secondary Outcomesmentioning
confidence: 99%